2020
DOI: 10.3390/molecules25092124
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Data and Computational Modeling of Baricitinib in Various (DMSO + Water) Mixtures

Abstract: The solubility and thermodynamic analysis of baricitinib (BNB) in various dimethyl sulfoxide (DMSO) + water mixtures were performed. The “mole fraction solubilities (xe)” of BNB in DMSO and water mixtures were determined at “T = 298.2–323.2 K” and “p = 0.1 MPa” using an isothermal saturation technique. “Hansen solubility parameters (HSPs)” of BNB, pure DMSO, pure water and “DMSO + water” mixtures free of BNB were also estimated. The xe data of BNB was regressed well by five different thermodynamics-based co-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The results of enthalpy and Gibbs free energy measurements were in accordance with solubility data of SIM in H 2 O and various micellar solutions of different non-ionic surfactants. The positive values of apparent standard enthalpy (Δ sol H 0 > 0) and apparent standard Gibbs energy (Δ sol G 0 > 0) in all samples suggested an endothermic dissolution/solubilization behavior of SIM in H 2 O and various micellar solutions of T80, T20, M52, M59, B35 and B58 [ 38 , 51 ]. The positive values of Δ sol H 0 and Δ sol G 0 might be due to the formation of new bond energy of attraction between the drug and solvent molecules [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of enthalpy and Gibbs free energy measurements were in accordance with solubility data of SIM in H 2 O and various micellar solutions of different non-ionic surfactants. The positive values of apparent standard enthalpy (Δ sol H 0 > 0) and apparent standard Gibbs energy (Δ sol G 0 > 0) in all samples suggested an endothermic dissolution/solubilization behavior of SIM in H 2 O and various micellar solutions of T80, T20, M52, M59, B35 and B58 [ 38 , 51 ]. The positive values of Δ sol H 0 and Δ sol G 0 might be due to the formation of new bond energy of attraction between the drug and solvent molecules [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The average Δ sol S 0 value for SIM dissolution/solubilization was recorded as 7.28 J mol -1 K -1 with uncertainty of 1.40. The positive Δ sol S 0 values for SIM showed an entropy-driven dissolution/solubilization behavior of SIM in H 2 O and various micellar solutions of T80, T20, M52, M59, B35 and B58 [ 51 ]. Finally, the dissolution/solubilization behavior of SIM was found to be endothermic and entropy-driven in H 2 O and various micellar solutions of T80, T20, M52, M59, B35 and B58 [ 36 , 38 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…As per the results recorded for solubility modeling, it was observed that all investigated models showed low RMSD s (average RMSD < 2.0%), which indicated good correlation of obtained solubility data of PPN with all investigated models. However, it should be noted that the error values of every model could not be compared with each other as each model was related with different parameters and model coefficients [ 49 ]. In general, the performance of all investigated models was good, but the “Jouyban–Acree model” could be considered as the most suitable model because it utilized the least number of model coefficients in addition to having a low RMSD value.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, HSPs for PPN, pure THP, pure water and various “THP + water” mixtures free of PPN were computed in this research. The δ value for PPN, pure THP and pure water was computed by applying Equation (3) [ 49 , 51 , 52 ] as follows: in which “ δ = total HSP; δ d = dispersion HSP; δ p = polar HSP and δ h = hydrogen-bonded HSP”. The HSPs for PPN, pure THP and pure water were estimated using “HSPiP software (version 4.1.07, Louisville, KY, USA)” [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation